2013
DOI: 10.1177/0300060512474569
|View full text |Cite
|
Sign up to set email alerts
|

9p21 Polymorphisms increase the risk of peripheral artery disease in the Han Chinese population

Abstract: Objective: A case-control study to investigate the association of the 9p21 single nucleotide polymorphisms (SNPs) rs10757274 and rs10757278 (known to be associated with coronary artery disease [CAD] risk) with peripheral arterial disease (PAD), in a Han Chinese population. Methods: The rs10757274 and rs10757278 genotypes of patients with PAD, and age-and sex-matched control subjects, were determined. Multivariate unconditional logistic regression analyses were performed, with adjustments for age, sex, hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Another study concluded that the risk allele, rs10757278(G), showed an increased association with MI and heart attacks both in general and, more specifically, in so-called early-onset MI ( 28 ). Furthermore, Tian et al ( 29 ) showed that the variant GG genotype was associated with an increased risk of peripheral artery disease as well as CAD. Holdt et al ( 30 ) showed that carrying 1 or 2 copies of chr9p21 risk allele confers more severe CVD, while Patel et al ( 25 ) noticed faster progression of CVD in the risk allele carriers than in individuals with 0 copies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that the risk allele, rs10757278(G), showed an increased association with MI and heart attacks both in general and, more specifically, in so-called early-onset MI ( 28 ). Furthermore, Tian et al ( 29 ) showed that the variant GG genotype was associated with an increased risk of peripheral artery disease as well as CAD. Holdt et al ( 30 ) showed that carrying 1 or 2 copies of chr9p21 risk allele confers more severe CVD, while Patel et al ( 25 ) noticed faster progression of CVD in the risk allele carriers than in individuals with 0 copies.…”
Section: Discussionmentioning
confidence: 99%
“…Age stratification analysis indicated that the effects of 9p21 on peripheral arterial disease and CAD may change with age. 26,27 Thus, the effects of 9p21 on IS may change with age. Second, this is the first identification of rs1333047 TT genotype that increases the susceptibility to IS for Chinese people.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that chromosome 1p31 locus is specific to peripheral arterial occlusive disease, which is diagnosed angiographically and/or surgically. Rs1333049 on chromosome 9p21 was not only associated with coronary artery disease (CAD) susceptibility, but also associated with PAD, which indicated that CAD and PAD might have a common genetic basis.…”
Section: Introductionmentioning
confidence: 99%